Community investment in old urban quarters: The case of a community based redevelopment process in Merkato, Addis Ababa - Terefe , Heyaw (Zede Journal of Ethiopian Engineers and Architects, 2023)
The history of urban development in Sub-Saharan Africa is dominated by disinvestment and weak investment. Even though that has been changing during the past decade due to improved economic performance, studies on investments in old areas of urban centers are quite scarce. A community-based process of investment in an old market district of Addis Ababa through the redevelopment approach was studied to contribute to reducing the gap. Historically, urban redevelopment was driven by property value decline and protection of the ‘public’ interests of health and safety. Its major investors were professional developers and the state. It was criticized for effects such as eviction, community fights, destruction of heritage, and visual ‘monotony’, and the criticisms have eventually led to emergence of more responsive approaches such as rehabilitation and conservation. The focus of this paper is on why the investor role, in the case of the study redevelopment, has shifted to the community and to what extent the shift has prevented the common effects of redevelopment. The study indicates that the drivers of much of the blight were macro-economic and policy factors rather than property value decline; the objectives of redevelopment have not been the classic public interests of health and safety: they were mainly the ‘grafted’ objectives of modernization, efficient use of land, and increasing tax revenue; and that the community based investment approach was able to prevent the effects of redevelopment only partly due to inadequate support by the state. The study was made by using a case study approach of interview, document review, and observation.